Factors influencing tax compliance among TikTok users engaged in e-commerce activities in Malaysia / Munawarah Mahran ... [et al.] - Mahran, Munawarah; Abdul Rashid, Siti Fatimah (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2023)
The Covid-19 pandemic has catalysed the growth of e-commerce, including using social media platforms for business. However, the lack of a physical presence in e-commerce introduces tax issues, potentially risking tax revenue losses. This study aimed to understand tax compliance among e-commerce operators in Malaysia who use TikTok. It examined the level of tax compliance, awareness, knowledge, morale, and complexity among these operators and explored the relationship between these factors and tax compliance. Data were collected via an online questionnaire and analysed from 106 responses using SPSS. The results indicated that TikTok users demonstrated a high level of tax compliance, solid tax knowledge, and strong morale but displayed low levels of tax awareness and complexity. Tax knowledge and morale positively influenced tax compliance among TikTok e-commerce operators in Malaysia, while tax awareness and complexity did not significantly affect compliance. These findings aid in understanding the behaviour of e-commerce operators regarding tax compliance, thereby promoting tax compliance and minimising potential tax revenue losses for the government.